2001
DOI: 10.1521/scpq.16.3.253.19892
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of the effects of escape and attention on students' compliance during instruction.

Abstract: This study examined three strategies for assessing compliance in students whose speech and language development were delayed. The effects of attention versus escape from instruction following compliance were examined through a descriptive assessment in the classroom, an out-of-class experimental analysis conducted by a consultant, and an inclass experimental analysis implemented by the teacher. The in-class analysis supported an attention-based intervention for all participants. The descriptive assessment data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…That is, while experts advocate for using a variety of procedures to collect information regarding behavior and the environmental conditions surrounding it, their lack of direct involvement may reduce the meaningfulness of their contributions to the outcome of the process. On the other hand, although individualized team members' experiences make them privy to pertinent information, they have not demonstrated an ability to develop reliable or valid hypotheses of function and, as some have suggested, may not be able to do so in the absence of a trained expert to lead the process (Conroy, Clark, Gable, & Fox, 1999;Noell, VanDerheyden, Gatti, & Whitmarsh, 2001;Stichter, Shellady, & Sealander, 2000). Thus, the barrier to expert-driven FBA seems to be the absence of information afforded by contact with the student, and the barrier to practitioner-driven FBA seems to be lack of fluency with the formalized processes and procedures necessary to perform an analysis of behavior.…”
Section: The Question Remainsmentioning
confidence: 99%
“…That is, while experts advocate for using a variety of procedures to collect information regarding behavior and the environmental conditions surrounding it, their lack of direct involvement may reduce the meaningfulness of their contributions to the outcome of the process. On the other hand, although individualized team members' experiences make them privy to pertinent information, they have not demonstrated an ability to develop reliable or valid hypotheses of function and, as some have suggested, may not be able to do so in the absence of a trained expert to lead the process (Conroy, Clark, Gable, & Fox, 1999;Noell, VanDerheyden, Gatti, & Whitmarsh, 2001;Stichter, Shellady, & Sealander, 2000). Thus, the barrier to expert-driven FBA seems to be the absence of information afforded by contact with the student, and the barrier to practitioner-driven FBA seems to be lack of fluency with the formalized processes and procedures necessary to perform an analysis of behavior.…”
Section: The Question Remainsmentioning
confidence: 99%
“…Staff training in collaborative FBA cannot be delivered successfully via a hit-and-run inservice model (Sailor et al, 2000). Instead, training must involve an introduction to the concept, with sufficient examples, followed by facilitation and continued support of the transition process (Noell, VanDerHeyden, Gatti, & Whitmarsh, 2001;Scott & Nelson, 1999a). The generic steps for performing a collaborative team-based FBA are presented in Table 1.…”
Section: Practical Steps For Implementing Changementioning
confidence: 99%
“…He then used lists of identified at-risk students to show the faculty that this amount of time is not sufficient to meet the comprehensive behavior support needs at King Elementary. In addition to effective example selection, training must facilitate generalization by providing multiple opportunities for follow-up training and troubleshooting (Conroy et al, 1999;Noell et al, 2001;Taylor-Green et al, 1997). Bridges (1991) suggested that in the typical system, a small group of individuals have the requisite skills to make the proposed changes and will often simply move ahead on their own.…”
Section: Ventionsmentioning
confidence: 99%
“…Teachers' instructions to students within the classroom, aid in the acquisition of both the students' academic and nonacademic skills. Teachers' commands promote verbal and social skills, and facilitate appropriate classroom behavior (Atwater & Morris, 1988;Ford, Olmi, Edwards & Tingstrom, 2001;Matheson & Shriver, 2005;Noell, VanDerHeyden, Gatti & Whitmarsh, 2001). In this respect, compliance to teacher commands is an integral aspect of classroom behavior management.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, throughout the vast array of command/compliance literature, only a few studies have studied commands in naturalistic classroom settings (Atwater & Morris, 1988;Matheson & Shriver, 2005;Ndoro, Hanley, Tiger, & Heal, 2006;Noell et al, 2001;Strain, Lambert, Kerr, Stagg, & Lenkner, 1983). Researchers have generally studied one command type at a time leading to the overlap in identification and description of commands and to some confusion regarding the role that command form, specificity, and rate play in a child's compliance to commands (Houlihan et al, 1992;Houlihan, Vincent, Ellison, & Jones, 1994).…”
Section: Introductionmentioning
confidence: 99%